DRIVING SUSTAINABILITY: EXPLORING GREEN INNOVATIONS IN THE UK AND INDONESIA’S MANUFACTURING INDUSTRIES - Mulyono, Richia Ruella (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Sustainability and green innovations are becoming integral components of modern business strategies, especially in the manufacturing sector. This paper aims to explore the adoption and implementation of green innovations in manufacturing industries in the United Kingdom (UK) and Indonesia. By conducting a comparative analysis of sustainable practices in both countries, this study highlights the similarities and differences in their approaches toward achieving environmental sustainability. The research investigates the challenges and opportunities faced by manufacturing companies in adopting green innovations and examines the impact of governmental regulations, economic conditions, and technological advancements. Findings from this research contribute to a deeper understanding of how sustainability strategies can drive economic growth and environmental preservation in both developed and developing economies.